Phytochemical evaluation and in-vitro antibacterial activity of ethanolic extracts of Moroccan Lavandula x intermedia leaves and flowers - JAMILA FLIOU; FEDERICA SPINOLA; OUASSIMA RIFFI; ASMAA ZRIOUEL; ALI AMECHROUQ; LUCA NALBONE; ALESSANDRO GIUFFRIDA; FILIPPO GIARRATANA (Society for Indonesian Biodiversity, 2023)
Abstract. Fliou J, Spinola F, Riffi O, Zriouel A, Amechrouq A, Nalbone L, Giuffrida A, Giarratana F. 2023. Phytochemical evaluation and in-vitro antibacterial activity of ethanolic extracts of Moroccan Lavandula x intermedia leaves and flowers. Biodiversitas 24: 5788-5796. This study performed a preliminary evaluation of the phytochemical composition and in vitro antibacterial activity of ethanolic extracts of Lavandula x intermedia leaves and flowers collected in the Fez-Meknes region of Morocco. Phytochemical analyses comprised qualitative colorimetric determinations of alkaloids, anthraquinones, and terpenes and quantitative analysis of total polyphenols, flavonoids, and condensed tannins by UV spectrophotometer. Antibacterial activity was evaluated by determining minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values against different ATCC bacterial strains. The phytochemical analysis showed a high amount of total polyphenols, flavonoids, and tannins in the leaf extract and a higher amount of terpenes based on colorimetric reaction than the flower extract. A positive colorimetric reaction for alkaloids and anthraquinones was detected for both extracts. The antibacterial activity of leaves and flower extract was not different against Gram-positive and Gram-negative strains (p<0.05). The results of the present study suggest the possible use of ethanolic extracts of L. x intermedia collected in the Fez-Meknes region of Morocco as a natural agent against bacterial pathogens.